Agrarian Community Empowerment Model Based on Digital Technology and Environmental Sustainability: A Case Study in Enrekang District - Suparman, Suparman; Syukur, Muhammad; S, Putriyani; Sitonda, Syawal (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2025)
The agricultural sector in Enrekang Regency faces challenges, including climate change, hilly topography, and low adoption of digital technology. These issues highlight the urgent need for research to develop a digital technology-based model to enhance productivity, economic welfare, and environmental sustainability. This study employed a mixed-methods approach, involving 500 farmers through quantitative surveys, in-depth interviews, and focus group discussions. Data analysis included t-tests and linear regression to assess model effectiveness, while thematic analysis explored social and cultural factors affecting implementation. Results showed increased onion productivity from 9 to 12 tons/hectare and coffee from 1.2 to 1.5 tons/hectare. Farmers’ income rose by 50%, with a 20% reduction in production costs. Using chemical fertilizers and irrigation decreased by 18% and 25%. Digital technology adoption increased from 12% to 68%, and community participation reached 89%. This model effectively improves productivity, welfare, and sustainability, providing a foundation for inclusive agricultural policy development.